The Vasoreparative Function of Myeloid Angiogenic Cells Is Impaired in Diabetes Through the Induction of IL1β. (9th March 2018) - Chambers, Sarah E. J.; O'Neill, Christina L.; Guduric‐Fuchs, Jasenka; McLoughlin, Kiran J.; Liew, Aaron; Egan, Aoife M.; O'Brien, Timothy; Stitt, Alan W.; Medina, Reinhold J.
Abstract: Myeloid angiogenic cells (MACs) promote revascularization through the paracrine release of angiogenic factors and have been harnessed as therapeutic cells for many ischemic diseases. However, their proangiogenic properties have been suggested to be diminished in diabetes. This study investigates how the diabetic milieu affects the immunophenotype and function of MACs. Both MACs isolated from diabetic conditions and healthy cells exposed to a diabetic environment were used to determine the potential of MACs as a cell therapy for diabetic‐related ischemia. MACs were isolated from human peripheral blood and characterized alongside proinflammatory macrophages M (LPS + IFNγ) and proangiogenic macrophages M (IL4). Functional changes in MACs in response to high‐d ‐glucose were assessed using an in vitro 3D‐tubulogenesis assay. Phenotypic changes were determined by gene and protein expression analysis. Additionally, MACs from type 1 diabetic (T1D) patients and corresponding controls were isolated and characterized. Our evidence demonstrates MACs identity as a distinct macrophage subtype that shares M2 proangiogenic characteristics, but can be distinguished by CD163 hi expression. High‐d ‐glucose treatment significantly reduced MACs proangiogenic capacity, which was associated with a significant increase in IL1β mRNA and protein expression. Inhibition of IL1β abrogated the antiangiogenic effect induced by high‐d ‐glucose. IL1β was also significantly upregulated in MACs isolated from T1D patients with microvascular complications compared to T1D patients without microvascular complications or nondiabetic volunteers. This study demonstrates that Type 1 diabetes and diabetic‐like conditions impair the proangiogenic and regenerative capacity of MACs, and this response is mediated by IL‐1β. Stem Cells 2018;36:834–843 Abstract : Myeloid angiogenic cells (MACs) phenotype becomes proinflammatory under diabetic conditions. Schematic summary of MACs shift in phenotype from proangiogenic to antiangiogenic induced by diabetes. MACs under diabetic‐like conditions show reduced expression of proangiogenic markers CD163 and CD204, and increased levels of IL1β.